Genetic Diversity, Population Structure, and Parentage Analysis of Croatian Grapevine Germplasm - Žulj Mihaljević, Maja (Genes (Basel), 2020)
Croatian viticulture was most extensive at the beginning of the 20th century, when about 400 varieties were in use. Autochthonous varieties are the result of spontaneous hybridization from the pre-phylloxera era and are still cultivated today on about 35 % of vineyard area, while some exist only in repositories. We present what is the most comprehensive genetic analysis of all major Croatian national repositories, with a large number of microsatellite, or simple sequence repeat (SSR) markers, and it is also the first study to apply single nucleotide polymorphism (SNP) markers. After 212 accessions were fingerprinted, 95 were classified as unique to Croatian germplasm. Genetic diversity of Croatian germplasm is rather high considering its size. SNP markers proved useful for fingerprinting but less informative and practical than SSRs. Analysis of the genetic structure showed that Croatian germplasm is predominantly part of the Balkan grape gene pool. A high number of admixed varieties and synonyms is a consequence of complex pedigrees and migrations. Parentage analysis confirmed 24 full parentages, as well as 113 half-kinships. Unexpectedly, several key genitors could not be detected within the present Croatian germplasm. The low number of reconstructed parentages (19%) points to severe genetic erosion and stresses the importance of germplasm repositories.